The Great Recession and Fertility in Europe: A Sub-National Analysis - Anna Matysiak; Daniele Vignoli; Tomáš Sobotka (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
This study investigates how the changes in labour market conditions and economic growth affected fertility before and during the recent economic recession in Europe. To this end, we use data for 258 European regions in 28 European Union (EU) member states and Iceland. We apply three-level growth-curve models which allow for a great deal of flexibility in modelling temporal change and handling hierarchically structured data. Our findings show that fertility decline was strongly related to unemployment increase and that this relationship was significant at all ages. Fertility responded to worsening economic conditions especially in Southern Europe and in Central and Eastern Europe, i.e. two broad regions which were considerably affected by the recession and where welfare policies provided lowest support against poverty and unemployment.
Keywords: 300; Fertility; economic uncertainty; economic recession; Europe; regional differences; unemployment